Catalyst Free Silica Templated Porous Carbon Nanoparticles from Bio-Waste Materials - Hegde, Gurumurthy; Kumar, Anuj; Shoriya Aruni, Abdul Manaf; Zainab, Ngaini; K. V., Sharma (Royal Society of Chemistry, 2014)
Porous Carbon Nanoparticles (PCNs) with well-developed micro-porosity were obtained from bio-waste oil palm leaves (OPL) using single step pyrolysis in nitrogen atmosphere at 500–600C in tube-furnace without any catalysis support. The key approach was using silica (SiO2) bodies of OPL as a template in the synthesis of microporous carbon nanoparticles with very small particle sizes of 35–85 nm and pore sizes between 1.9–2 nm.